Preventing a new invasive alien plant from entering and spreading in the Euro‐Mediterranean region: the case study of Parthenium hysterophorus. (December 2014) - Brunel, S.; Panetta, D.; Fried, G.; Kriticos, D.; Prasad, R.; Lansink, A. O.; Shabbir, A.; Yaacoby, T.
<x xml:space="preserve">Abstract</x> Parthenium or famine weed (Parthenium hysterophorus L.) is an annual plant originating from the Americas, which is a major invasive alien plant in almost all continents. While the deleterious impacts of the species on agriculture, human and animal health have been well documented, information on the pathways of entry of the species is only occasionally mentioned in the literature. As this invasive alien plant is only recorded as established in Israel and Egypt within the Euro‐Mediterranean region, the European and Mediterranean Plant Protection Organization identified P. hysterophorus as an emerging threat. EPPO therefore performed a Pest Risk Analysis on this species to assess the risk it represents and to consider appropriate management options. The EPPO Pest Risk Analysis main outputs are summarized in this article, indicating the probability of entry of the species via the different pathways within the EPPO region, its probabilities of establishment and spread, and the magnitude of its potential agricultural, environmental and social impacts.